Thinning Southern Pines - A Key to Greater Returns - Chris Demers; Alan Long; Jarek Nowak (EDIS)
Revised! SS-FOR-24, a 6-page fact sheet by Chris Demers, Alan Long, and Jarek Nowak, reviews the underlying concepts of stand density, crown position, and forest health before describing specific methods of thinning, as well as when and how to thin. Includes references. Published by the UF School of Forest Resources and Conservation, December 2006.